PENGARUH MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN TERHADAP PERKEMBANGAN SPIRITUALITAS SISWA-SISWI SEKOLAH MENENGAH ATAS PADA ERA MILENIAL - Axel William Fritz Setiawan; Sinta Susilo; Videlva Aracelly Hartanto (Bethel Press, 2020)
Children's spirituality is an important thing that must receive more attention from parents. This value must be instilled in children from an early age because the child's spiritual development will determine his relationship with God and others. Christian spirituality refers to a spiritual life led by the Holy Spirit to trust and love Jesus Christ in one's life increasingly. This research aims to internalize Christian religious values in students. The research method we use is a descriptive qualitative analysis method, with the instrument being a questionnaire created using Google Forms. Our research concluded that Christian religious education can influence the spiritual development of high school students in the millennial era. When teaching, teachers must remind them about how good God is and how miracles He has given so that they can feel calm and peaceful in facing all obstacles because God is always with them and strengthens their hearts in carrying out all the problems they face. However, some still feel that Christian religious education does not affect the development of spirituality because technology is increasingly advanced, so what God wants is not following their wishes, so they decide to stay away from it. Some of the material provided is increasingly difficult, so high school students need help understanding it. The hope is that this article can guide Christian Religious Education teachers who will teach so that they always experience improvisation in their teaching.